Inverse Calibration of Confinement and Softening in RC Beam-Column Joints for Improved DSFM Predictions - Yilmaz, Mehmet Ozan (MDPI, 2026)
Standard compatibility-based truss models, including the Disturbed Stress Field Model (DSFM), often underestimate the shear strength and deformation capacity of reinforced-concrete (RC) beam-column joints. This study investigates the origin of this bias through a systematic inverse identification framework and derives joint-core constitutive relationships tailored to the highly confined, nonuniform stress states of joints. Inverse analyses show that improving confinement effectiveness alone leads to unrealistic parameter saturation and cannot reproduce the measured energy absorption, indicating that conventional compression-softening formulations remain excessively punitive for joint cores. When confinement activation and softening are identified simultaneously, a clear mechanism shift emerges: unlike panel-based theories that link softening to tensile-cracking measures (principal strain ratio), joint softening is overwhelmingly governed by the principal compressive strain, consistent with crushing-dominated damage accumulation. Based on these trends, unified power-law expressions are proposed for both passive confinement activation and damage-induced softening as functions of principal compressive strain only, adhering to a parsimonious formulation without auxiliary variables such as concrete strength or reinforcement ratio (R2 approximate to 0.89). The model is validated on an independent database of 113 specimens, including high-strength concrete and exterior joints, eliminating the systematic conservatism of the standard DSFM and improving the mean experimental-to-predicted strength ratio from 0.85 to 1.01 while reducing the coefficient of variation from 34.5% to 13%. The proposed formulation supports more reliable joint shear backbone predictions for seismic assessment of RC frame buildings.
Keywords: reinforced concrete beam-column joints; joint shear strength; Disturbed Stress Field Model (DSFM); compression softening; confinement effectiveness; inverse identification; constitutive modeling; experimental database validation; REINFORCED-CONCRETE; SHEAR-STRENGTH; MODEL; CONNECTIONS; DEFORMATION; PARAMETERS; ALGORITHM; BEHAVIOR; FAILURE; CURVES; Construction & Building Technology; Engineering